2022
DOI: 10.3389/fimmu.2022.983934
|View full text |Cite
|
Sign up to set email alerts
|

Case report: CD19-directed CAR-T cell therapy combined with BTK inhibitor and PD-1 antibody against secondary central nervous system lymphoma

Abstract: Current therapeutic strategies for central nervous system (CNS) relapse of diffuse large B-cell lymphoma (DLBCL) are extremely limited. Secondary central nervous system lymphoma (SCNSL) also shows a grave prognosis and high mortality. This report describes a young female patient with DLBCL and CNS relapse who received low-dose CD19-directed chimeric antigen receptor T (CAR-T) cell therapy followed with Bruton’s tyrosine kinase inhibitor and programmed cell death protein 1 antibody after several lines of chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…While no infection was observed in patients receiving PD-1 maintenance after CAR-T therapy [ 15 ]. Furthermore, Zhang et al [ 16 ] reported one case who received BTK and PD-1 inhibitors maintenance therapy after CD19-directed CAR-T developed no infection but only menorrhagia and anemia. In this case, no adverse events including infection were observed during the 1-year maintenance therapy with BTK and PD-1 inhibitors which was consistent with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…While no infection was observed in patients receiving PD-1 maintenance after CAR-T therapy [ 15 ]. Furthermore, Zhang et al [ 16 ] reported one case who received BTK and PD-1 inhibitors maintenance therapy after CD19-directed CAR-T developed no infection but only menorrhagia and anemia. In this case, no adverse events including infection were observed during the 1-year maintenance therapy with BTK and PD-1 inhibitors which was consistent with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the second-generation BTKis with highly selective binding capacity and fewer off-target effects, have been explored for the treatment of R/R PCNSL. For instance, zanubrutinib has shown clinical efficacy when used in combination with chemotherapy or cell therapy ( 15 , 16 ). Tirabrutinib, an irreversible BTKi approved in Japan ( 17 ), resulted in an ORR of 63.6% and a median PFS of 2.9 months in a phase I/II study ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent radiation treatment for endometrial cancer was delayed due to the Covid-19 pandemic. Nonetheless, follow-up examinations indicated no recurrence of symptoms, and complete remission (CR) was achieved approximately 18 months following CD19 CAR-T cell treatment (137).…”
Section: Cd-19 Directed Car-t Cell Based Combination Immunotherapymentioning
confidence: 99%